2002
DOI: 10.1016/s0920-9964(01)00372-3
|View full text |Cite
|
Sign up to set email alerts
|

An MRI study of temporal lobe abnormalities and negative symptoms in chronic schizophrenia

Abstract: Previous magnetic resonance imaging (MRI) studies have reported various subtle brain abnormalities in schizophrenic patients, including temporal lobe abnormalities, which are of particular interest given the role of this brain region in auditory and language processing, and the characteristic deficits in these processes in schizophrenia. Subjects in this study were 16 male patients diagnosed with chronic schizophrenia and 15 healthy male comparison subjects. These patients were characterized by negative sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
59
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(70 citation statements)
references
References 55 publications
10
59
0
1
Order By: Relevance
“…Investigation of the functional correlates of FA in the uncinate fasciculus revealed significant inverse correlations with negative symptoms, including alogia and affective flattening. Our results thus converge with prior studies reporting an association between temporal gray (Anderson et al, 2002) and white (Sigmundsson et al, 2001) matter volumetric deficits and negative symptoms in patients with schizophrenia. Moreover, lower FA in this region correlated significantly with worse memory functioning.…”
Section: Discussionsupporting
confidence: 91%
“…Investigation of the functional correlates of FA in the uncinate fasciculus revealed significant inverse correlations with negative symptoms, including alogia and affective flattening. Our results thus converge with prior studies reporting an association between temporal gray (Anderson et al, 2002) and white (Sigmundsson et al, 2001) matter volumetric deficits and negative symptoms in patients with schizophrenia. Moreover, lower FA in this region correlated significantly with worse memory functioning.…”
Section: Discussionsupporting
confidence: 91%
“…Neuroimaging studies report reductions in amygdalar volumes in schizophrenic patients (Rajarethinam et al, 2001, Anderson et al, 2002. In addition, fMRI studies revealed reduced amygdalar activation in schizophrenic subjects when evaluating facial expressions for emotional salience (Gur et al, 2002, Hempel et al, 2003 and this impairment appears to be specific to patients with primary negative symptoms (Anderson et al, 2002).…”
Section: Discussionmentioning
confidence: 97%
“…29 In humans, hippocampal abnormalities have been identified as important susceptibility factors for schizophrenia. [30][31][32][33][34] Recently, extensive studies have been focusing on information-processing deficits, as manifested by sensorimotor gating, in schizophrenia and other neuropsychiatric disorders. Nevertheless, how hippocampal abnormalities contribute to information-processing deficits remains to be explicated.…”
Section: Discussionmentioning
confidence: 99%